Effect of Liquidity, Solvency, Company Size, and Company Age on Audit Report Lag - Cindy Febrian Theng; Peng Wie (eCo-Buss, 2022)
The purpose of this study was to examine the factors that influence audit report lag. The factors tested in this study are liquidity, solvency, company size and age of the company against audit report lag in energy sector companies listed on the Indonesia Stock Exchange for the 2017-2020 period. The sampling technique in this study is purposive sampling with a total population of 69 energy sector companies listed on the IDX for the 2017-2020 period, which then obtained 48 samples. The data is secondary data and performed descriptive statistical test, classical assumption test, multiple linear regression analysis, t test, and f test with the help of SPSS version 25 software. Based on the results of this study indicate that liquidity has no effect on audit report lag, solvency has a significant effect on audit report lag, company size has a significant effect on audit report lag, company age has a significant effect on audit report lag, liquidity, solvency, company size, and company age simultaneously have a significant effect on audit report lag